Journalism of ideas : brainstorming, developing, and selling stories in the digital age - Reimold, Daniel
"Journalism of Ideas is a comprehensive field guide for brainstorming, discovering, reporting, digitizing, and pitching news, opinion, and feature stories within journalism 2.0. With on-the-job advice from professional journalists, activities to sharpen your multimedia reporting skills, and dozens of story ideas ripe for adaptation, Dan Reimold helps you develop the journalistic know-how that will set you apart at your campus media outlet and beyond.The exercises, observations, anecdotes, and tips in this book cover every stage of the story planning and development process, including how news judgment, multimedia engagement, records and archival searches, and various observational techniques can take your reporting to the next level. Separate advice focuses on the storytelling methods involved in data journalism, photojournalism, crime reporting, investigative journalism, and commentary writing. In addition to these tricks of the trade, Journalism of Ideas features an extensive set of newsworthy, timely, and unorthodox story ideas to jumpstart your creativity. The conversation continues on the author's blog, College Media Matters.Reimold also shows students how to successfully launch a career in journalism: the ins and outs of pitching stories, getting your work published, and navigating the post-graduation job search. Related sections of the book highlight the art of freelancing 2.0, starting an independent site, blogging, constructing quality online portfolios, securing internships, and building a social media following. "--